75.1k views
2 votes
If anyone answers this is a BEAST !Justify each step of the solution by stating the property that was used to get to each step. Given: 4(-6x – 3) + 24x = -72x + 132 Step 1: -24x – 12 + 24x = -72x + 132 Step 2: –12 = -72x + 132 Step 3: -144 = -72x Step 4: 2 = x

User Turgut
by
5.7k points

1 Answer

7 votes

4(-6x – 3) + 24x = -72x + 132

Step 1 -24x – 12 + 24x = -72x + 132 Distribute Property of Equality

Step 2: –12 = -72x + 132 equivalent

Step 3: -144 = -72x Subtraction Property of equality

Step 4: 2 = x Equivalent / Division property of equality


User GriFlo
by
6.4k points